Drones : the brilliant, the bad and the beautiful - Miah, Andy, 1975- (Emerald Publishing Limited, 2020)
Against the backdrop of an increasingly dynamic world, driven by rapid digital innovation and technological advances, drones are becoming prolific within society. In this book, Andy Miah delivers a comprehensive analysis of the wide-reaching applications of drones, as well as a critical interrogation of the social, cultural and moral issues that they provoke. Delving into philosophical discussions about the implications of drone technology, this book shines a light on their real-world applications, the challenges they pose, and what they reveal about the human condition, when faced with a future of autonomous, intelligent robots.
Includes index.
Keywords: Drone aircraft -- Social aspects.; Drone aircraft -- Moral and ethical aspects.; Drone aircraft -- Technological innovations.; Technology & Engineering, Aeronautics & Astronautics.; Aerospace & aviation technology.; elektronické knihy; electronic books